2008
DOI: 10.1016/j.chembiol.2008.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Polo-like Kinase 1 by Blocking Polo-Box Domain-Dependent Protein-Protein Interactions

Abstract: The serine/threonine kinase Polo-like kinase 1 (Plk1) is overexpressed in many types of human cancers, and has been implicated as an adverse prognostic marker for cancer patients. Plk1 localizes to its intracellular anchoring sites via its polo-box domain (PBD). Here we show that Plk1 can be inhibited by small molecules which interfere with its intracellular localization by inhibiting the function of the PBD. We report the natural product thymoquinone and, especially, the synthetic thymoquinone derivative Polo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
223
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 217 publications
(231 citation statements)
references
References 35 publications
6
223
0
2
Order By: Relevance
“…S2e). Further, this binding was only partially sensitive to the Plk-1 Polo-box-domain-targeting drug thymoquinone 17 ( Supplementary Fig. S2f), suggesting that other parts of the protein outside of the Polo-box domain are involved in the interaction.…”
Section: Resultsmentioning
confidence: 99%
“…S2e). Further, this binding was only partially sensitive to the Plk-1 Polo-box-domain-targeting drug thymoquinone 17 ( Supplementary Fig. S2f), suggesting that other parts of the protein outside of the Polo-box domain are involved in the interaction.…”
Section: Resultsmentioning
confidence: 99%
“…Actually, several novel Plk1 inhibitors have been reported (28 -32), and some of them have proceeded to clinical trials (28,31). While this manuscript was in preparation, another group independently reported that thymoquinone and its derivative have an inhibitory activity to PBD-dependent recognition (52). Their compounds also induced Plk1 mislocalization, chromosomal congression defect, mitotic arrest, and apoptosis at a similar concentration to that for PPG.…”
Section: Discussionmentioning
confidence: 99%
“…These inhibitors induced mitotic arrest and apoptosis in HeLa cells 248 . Rosmarinic acid and salvianolic acids blocked some interactions of the SH2 domain of Src-family tyrosine kinases with labelled peptides that were designed to mimic the binding domain of the erythropoietin receptor 255 .…”
Section: Protein Protein Interactions Protein Protein Interactions Amentioning
confidence: 99%
“…Thymoquinone, and its synthetic derivative poloxin inhibited the interaction between polo-like kinase 1 and its intracellular anchoring site 248 .…”
Section: Protein Protein Interactions Protein Protein Interactions Amentioning
confidence: 99%
See 1 more Smart Citation